Analisis Yuridis Kepemilikan Hak Atas Tanah Melalui Perjanjian Nominee Oleh Warga Negara Asing di Indonesia (Studi Putusan Perkara Nomor: 2959 K/Pdt/2022) - Ada, Rosyani; Safik, Akhmad (UNES Law Review, 2023)
The focus of this research is Decision No. 2959 K/Pdt/2022 relating to the practice of legal smuggling through the use of a nominee agreement between a foreigner (Louise Marie France) and an Indonesian citizen (Desak Nyoman Kartini) in the acquisition of a plot of land as stated in Certificate of Title No. 5030 located in the Jimbaran area, Bali. Afterwards, Desak Nyoman Kartini transferred the land to a third party through a sale and purchase transaction without the knowledge of the foreign party (Louise Marie France). The main purpose of writing this article is to examine the regulations regarding the ownership of land rights and nominee agreements in the ownership of land rights by foreigners in Indonesia. In addition, this research aims to assess the suitability of Supreme Court Decision No.2959 K/Pdt/2022 with Law No.5/1960 and its implementing regulations in Indonesia. This research uses the normative legal method (yuridis normatif), which examines and analyzes norms in the form of laws and court decisions. The research findings show that Decision Number 2959 K/Pdt/2022 has not fully complied with the provisions stipulated in Law No.5/1960 and its implementing regulations, thus not providing legal certainty for justice seekers.